2019
DOI: 10.1021/acs.nanolett.8b04207
|View full text |Cite
|
Sign up to set email alerts
|

Highly Conductive Metallic State and Strong Spin–Orbit Interaction in Annealed Germanane

Abstract: Similar to carbon, germanium exists in various structures such as three-dimensional crystalline germanium and germanene, a two-dimensional germanium atomic layer. Regarding the electronic properties, they are either semiconductors or Dirac semimetals. Here, we report a highly conductive metallic state in thermally annealed germanane (hydrogen-terminated germanene, GeH), which shows a resistivity of ∼10–7 Ω·m that is orders of magnitude lower than any other allotrope of germanium. By comparing the resistivity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 64 publications
2
56
0
Order By: Relevance
“…These characteristics hold great promise for electronic and optoelectronic applications and recently we reported the first realization of germanane field effect transistors,f abricated from multilayer single crystal flakes, which demonstrated transport in both electron and hole doped regimes,w ith an on/off current ratio of up to 10 5 (10 4 ) and carrier mobilities of 150 cm 2 V À1 s À1 (70 cm 2 V À1 s À1 )a t 77 K( room temperature). [9] Moreover,i naseparate study [10] we found evidence for ah ighly conductive metallic state that develops with the dehydrogenation during heating, ap rocess,w hich seems to transform germanane thin flakes into multilayer germanene. These results as well as many other recently proposed applications of germanane [8a,11] and germanene [12] in (opto)electronics,e nergy production and storage as well as in (photo)catalysis leave no doubt that alarge scale,low cost and fast synthesis for very high quality and thermally stable germanane flakes is urgently required in order to fully explore the scientific and technological potential of 2D germaniumbased materials.…”
Section: Introductionmentioning
confidence: 79%
“…These characteristics hold great promise for electronic and optoelectronic applications and recently we reported the first realization of germanane field effect transistors,f abricated from multilayer single crystal flakes, which demonstrated transport in both electron and hole doped regimes,w ith an on/off current ratio of up to 10 5 (10 4 ) and carrier mobilities of 150 cm 2 V À1 s À1 (70 cm 2 V À1 s À1 )a t 77 K( room temperature). [9] Moreover,i naseparate study [10] we found evidence for ah ighly conductive metallic state that develops with the dehydrogenation during heating, ap rocess,w hich seems to transform germanane thin flakes into multilayer germanene. These results as well as many other recently proposed applications of germanane [8a,11] and germanene [12] in (opto)electronics,e nergy production and storage as well as in (photo)catalysis leave no doubt that alarge scale,low cost and fast synthesis for very high quality and thermally stable germanane flakes is urgently required in order to fully explore the scientific and technological potential of 2D germaniumbased materials.…”
Section: Introductionmentioning
confidence: 79%
“…Partially refined atomic coordinates and isotropic displacement factors for germanane at 295 K. Hydrogen positions were generated by geometrical considerationsand not refined.Space group C2: a = 6.789-(10) , b = 4.035(5) , c = 11.24(4) , b = 105.5(2)8 8.…”
mentioning
confidence: 99%
“…Apart from the most widely investigated material, graphene (monolayer of sp 2 carbon), there are a host of 2D materials that have garnered interest, including transition metal dichalcogenide (MX 2 ), MXene (M n+1 AX n ), silicene, phosphorene (i.e., black phosphorous), and germanene. Table 1 summarizes the typical electronic properties (bandgap (eV) [27][28][29][30][31][32] and work function (eV)), [33][34][35][36][37][38] structural property (bond length (Å)), [39][40][41][42][43][44] transport properties (electrical conductivity (S cm −1 ) [45][46][47][48][49][50] and thermal conductivity (W m −1 K −1 ) [51][52][53][54][55] ), mechanical in-plane stiffness (Young's modulus (GPa) [56][57][58][59][60][61] ), and surface energy (mJ m −2 ) [62][63][64][65][66] of these representative 2D materials.…”
Section: Physical Properties and Attractive Features Of 2d Materials mentioning
confidence: 99%
“…Mater. 2020, 32,1907006 [28] ≈1.80 (Sc 2 CO 2 ) [28] ≈0.88 (Zr 2 CO 2 ) [28] ≈1.0 (Hf 2 CO 2 ) [28] ≈1.27 (ML) [29] ≈0.55 (BL) [30] ≈1.88 (ML) [31] 0 (ML) [32] ≈0.05 (BL) [32] Work function a) [Φ, eV] ≈4.5 ≈5.1 (ML, BL, MoS 2 ) [33,34] ≈4.3 (ML, WS 2 ) [34] ≈4.6 (ML, WSe 2 ) [34] ≈4.37 (Ti 3 C 2 T X ) [35] ≈3.35 (Sc10C9) [36] ≈4.76 [37] ≈5.16 (ML) [38] ≈4.56 (FL) [38] 4.66 [37] Bond length [Å] 1.42 (C-C) ≈3.15-4.03 [39] ≈2.10 (Ti-C) [40] ≈1.99 (Ti-O) [41] ≈2.15 (Ti-F) [41] ≈2.25 (Si-Si) [42] ≈2.22 (P-P) [43] 2.49-2.56 (Ge-Ge) [44] Electroconductivity [S cm −1 ] ≈10 6 [45] ≈5.0 (MoS 2 ) [46] ≈10 4 [47] 6.5 kΩ b) [48] ≈300 (with graphene) [49] ≈10 5 [50] Thermal conductivity [W m −1 K −1 ] 5300 [51] ≈19.5 (MoS 2 ) [46] ≈55.2 (Ti 3 C 2 T X ) [52] ≈16 [53,54] 2000-5000 [55] ≈15.95 [54] Young's modulus [GPa] ≈1000 [56] ≈270 (MoS 2 ) [57] ≈330 ± 30 (Ti 3 C 2 T X ) [58] ≈82...…”
Section: Fibers (1d)mentioning
confidence: 99%